Fundamentals of real exchange rate in Costa Rica (2001-2014) - Fonseca Hernández, Raúl (2017)
This paper is aimed at helping social science professionals understand the behavior of the Costa Rican Real Exchange Rate Index (ITCER) regarding its fundamentals. The Behavioral Equilibrium Exchange Rate (BEER) is the theoretical model used to identify and analyze the effects of these variables on the ITCER. The six indicators analyzed were terms of trade, tax absorption, foreign direct investment (FDI), domestic real interest rate, and economy relative productivity. These indicators adequately explain the behavior of the real exchange rate, despite their variability. Two periods are clearly identified in the behavior of the ITCER: the first one (2001 - 2005) is a depreciation period while the second one (2006 - 2004) includes an appreciation process of the Costa Rican colon in real terms.